THE HUMANITARIAN MEANING IN HAYYA THE POWER OF LOVE 2: A BARTHESIAN VISUAL SEMIOTICS APPROACH - Purbaningrum, Aisyah Dias; Belasunda, Riksa; Pramana Koesoemadinata, Mohammad Isa; Astuti, Tri (Jurnal Ilmiah Bina Bahasa, 2025)
Despite growing interest in visual emotion in Indonesian cinema, limited attention has been paid to how religious–humanist films visualize humanitarian meaning; this study addresses that gap through an analysis of Hayya: The Power of Love 2. Narratively, this film is rooted in the real-world issue of Palestine, providing an empirical context for visually examining the humanitarian dimension. This study analyzes how mise-en-scène generates humanitarian meaning in Hayya: The Power of Love 2 (2019). A qualitative–descriptive approach is applied within Roland Barthes’s semiotic framework at the levels of denotation and connotation. Data were collected through shot-by-shot observation and visual note-taking, analyzed using denotative–connotative coding and occurrence mapping to identify patterns of meaning. The unit of analysis consists of shots or frames from purposively selected key scenes. Overall, the findings show that in-frame arrangements consistently guide interpretations toward humanitarian themes—especially vulnerability, solidarity, and an ethics of care—through relations among visual signs rather than reliance on dialogue. The study contributes to visual semiotics and humanitarian representation by demonstrating how recurring spatial, chromatic, and embodied cues organize and naturalize humanitarian concern in Indonesian religious–humanist cinema.